2021
DOI: 10.3390/educsci11080431
|View full text |Cite
|
Sign up to set email alerts
|

Career Exploration as Social and Emotional Learning: A Collaborative Ethnography with Spanish Children from Low-Income Contexts

Abstract: Children’s career exploration is a critical aspect of career development. Through it, children explore the interplay between their different life roles, including those related to work (in a broad sense), learning, and education. Through career exploration, children can (re)construct the emotions derived from the interactions between personal and contextual factors by giving meaning to life experiences. This process involves cognitive and affective activities. Evidence suggests that children from low-income co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Parents also influenced the career development level of primary school learners. Romero-Rodríguez et al (2021) found that parents with career exploratory learning provisions could improve the career development and future aspirations of children. Learners could accept the entailing situations and make the families the relevant and required models for them.…”
Section: Discussionmentioning
confidence: 99%
“…Parents also influenced the career development level of primary school learners. Romero-Rodríguez et al (2021) found that parents with career exploratory learning provisions could improve the career development and future aspirations of children. Learners could accept the entailing situations and make the families the relevant and required models for them.…”
Section: Discussionmentioning
confidence: 99%
“…To address the aims of this study, we implemented a qualitative research design based on the analysis of five interviews conducted using My System of Career Influences (MSCI) [49,50]. This tool has already been used in other qualitative studies, proving to be reliable in the study of career influences [51][52][53][54][55].…”
Section: Methodsmentioning
confidence: 99%
“…Children's relationships are established in this mediated digital landscape. Digital technologies are part of the subjective construction of these children, where they are already born, dealing with this new reality, involved in a kind of "nervous game" (Green & Bigum, 1993;Romero-Rodríguez et al, 2021;Moreno-Morilla et al, 2021). Digital technologies are to the new generations, as natural as the air we breathe and children form their mental schemas based on these technologies.…”
Section: Introductionmentioning
confidence: 99%